2004
DOI: 10.1007/s00421-004-1126-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficiency of warming devices during neonatal surgery

Abstract: This study assessed the relative efficiency of different warming devices (surgical sheets covering the body and a tubegauze on the head, forced-air warming, warming mattress) commonly used to prevent body hypothermia during neonatal surgery. Dry heat losses were measured from a thermal manikin, which simulated a low-birth-weight neonate of 1,800 g. The manikin's surface temperatures (35.8 degrees C) corresponded to those of neonates nursed in closed incubators. Experiments were performed in a climatic chamber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…The authors of one paper described water mattresses as reasonably effective in rewarming hypothermic infants, although this study was only observational with no other active treatment group for comparison [121]. Most comparative studies in children have shown inferior performance of water mattress warming against forced-air warming [122] and water garments [123], which accords with studies in adults.…”
Section: Circulating Water Devicesmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors of one paper described water mattresses as reasonably effective in rewarming hypothermic infants, although this study was only observational with no other active treatment group for comparison [121]. Most comparative studies in children have shown inferior performance of water mattress warming against forced-air warming [122] and water garments [123], which accords with studies in adults.…”
Section: Circulating Water Devicesmentioning
confidence: 94%
“…These are, however, more expensive than other warming methods [108]. Only a handful of studies have tested the use of water mattresses or garments in paediatric cases [121][122][123]. The authors of one paper described water mattresses as reasonably effective in rewarming hypothermic infants, although this study was only observational with no other active treatment group for comparison [121].…”
Section: Circulating Water Devicesmentioning
confidence: 99%
“…(8) described benefit of convection heating over radiant in rewarming 24 children after cardiac bypass procedures. Subsequent reports have been disappointing either because they were: retrospective reviews [(9) 25 children having cardiac bypass surgery], gave almost no details about methodology – including technique of warming – device, temperature and so [(10) 10 children, (2) 17 neonates, correspondence] or used techniques known to give inaccurate results (3,10). Szmuk et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has proven difficult to reverse this, particularly during long procedures in young children with open body cavities. It has been common practice to raise ambient temperature ( T ambient ) in pediatric theaters – the exact extent of this varying from institution to institution [25°C (2) to 30°C (3)]. Significant elevation increases the discomfort for staff, decreases their performance and has a potentially negative impact on the outcome of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Normal body temperature is maintained by balancing heat loss with heat gain. 5,9,10 Because of these risk factors, heat exchange between the body and the surrounding environment is greater for an infant than for an adult. Infants have a larger body surface area in relation to body mass ratio.…”
mentioning
confidence: 99%